Functional Dependence between Septal Protein SepJ from Anabaena sp. Strain PCC 7120 and an Amino Acid ABC-Type Uptake Transporter - Escudero, Leticia (J Bacteriol, 2016)
In the diazotrophic filaments of heterocyst-forming cyanobacteria, two different cell types, the CO(2)-fixing vegetative cells and the N(2)-fixing heterocysts, exchange nutrients, including some amino acids. In the model organism Anabaena sp. strain PCC 7120, the SepJ protein, composed of periplasmic and integral membrane (permease) sections, is located at the intercellular septa joining adjacent cells in the filament. The unicellular cyanobacterium Synechococcus elongatus strain PCC 7942 bears a gene, Synpcc7942_1024 (here designated dmeA), encoding a permease homologous to the SepJ permease domain. Synechococcus strains lacking dmeA or lacking dmeA and expressing Anabaena sepJ were constructed. The Synechococcus dmeA mutant showed a significant 22 to 32% decrease in the uptake of aspartate, glutamate, and glutamine, a phenotype that could be partially complemented by Anabaena sepJ. Synechococcus mutants of an ATP-binding-cassette (ABC)-type transporter for polar amino acids showed >98% decreased uptake of glutamate irrespective of the presence of dmeA or Anabaena sepJ in the same strain. Thus, Synechococcus DmeA or Anabaena SepJ is needed to observe full (or close to full) activity of the ABC transporter. An Anabaena sepJ deletion mutant was significantly impaired in glutamate and aspartate uptake, which also in this cyanobacterium requires the activity of an ABC-type transporter for polar amino acids. SepJ appears therefore to generally stimulate the activity of cyanobacterial ABC-type transporters for polar amino acids. Conversely, an Anabaena mutant of three ABC-type transporters for amino acids was impaired in the intercellular transfer of 5-carboxyfluorescein, a SepJ-related property. Our results unravel possible functional interactions in transport elements important for diazotrophic growth. IMPORTANCE Membrane transporters are essential for many aspects of cellular life, from uptake and export of substances in unicellular organisms to intercellular molecular exchange in multicellular organisms. Heterocyst-forming cyanobacteria such as Anabaena represent a unique case of multicellularity, in which two cell types exchange nutrients and regulators. The SepJ protein located at the intercellular septa in the filaments of Anabaena contains a permease domain of the drug/metabolite transporter (DMT) superfamily that somehow contributes to intercellular molecular transfer. In this work, we have found that SepJ stimulates the activity of a polar amino acid uptake transporter of the ATP-binding-cassette (ABC) superfamily, which could itself affect an intercellular transfer activity related to SepJ, thus unraveling possible functional interactions between these different transporters.